2018
DOI: 10.5603/arm.a2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin Inhibitors as a New Approach in the Treatment of Right Heart Failure in the Course of Chronic Obstructive Pulmonary Disease

Abstract: The aim of the study was to find out scientific evidence on the possible use of the combined angiotensin II receptor antagonist and neprilysin inhibitors (ARNI) in patients with right heart failure (RHF) in the course of chronic obstructive pulmonary disease (COPD). It has been proven that a lack of neprilysin or its reduced expression in hypoxia leads to exacerbation of pulmonary arterial remodelling (PAR) or pulmonary hypertension (PH) in the mechanism related to the platelet-derived growth factor (PDGF) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Natriuretic peptides are secreted and degraded in the lungs, and a number of studies have shown that their concentration is increased in the setting of PH. 12 In a study using a rodent model of hypoxemia-induced PH, sacubitril/valsartan was shown to significantly reduce right ventricular pressure and right ventricular dilatation. 13 Zern et al described five inotrope-dependent HFrEF patients listed for heart transplant in whom sacubitril/valsartan initiation resulted in reduced PVR within 24 h. 14 A proof of concept trial of acute neprilysin inhibition for PAH demonstrated a swift 14% fall in PVR.…”
Section: Discussionmentioning
confidence: 99%
“…Natriuretic peptides are secreted and degraded in the lungs, and a number of studies have shown that their concentration is increased in the setting of PH. 12 In a study using a rodent model of hypoxemia-induced PH, sacubitril/valsartan was shown to significantly reduce right ventricular pressure and right ventricular dilatation. 13 Zern et al described five inotrope-dependent HFrEF patients listed for heart transplant in whom sacubitril/valsartan initiation resulted in reduced PVR within 24 h. 14 A proof of concept trial of acute neprilysin inhibition for PAH demonstrated a swift 14% fall in PVR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results obtained in adult rats with the combined use of a neprilysin inhibitor and an angiotensin receptor blocker, mice deficient in neprilysin from birth are more prone to remodel their pulmonary vessels in response to chronic hypoxia compared to their littermate controls 28 . While some of this difference could be explained by interspecies differences, or by the effects of knockout versus pharmacological inhibition, the pleiotropic functions of ANP and other natriuretic peptides in the heart and in the vascular system that are independent of blood pressure regulation could also explain this discrepancy 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a reasonable concern that neprilysin inhibitors may increase the level of bradykinin in the lungs and exacerbate symptoms in patients suffering from asthma or COPD. On the other hand, neutral endopeptidase 24.11 causes an increase in the level of natriuretic peptides having bronchodilatory and immunosuppressive properties, which could lessen the effect of bradykinin action [5]. Moreover, there are studies suggesting that natriuretic peptides, as natural antagonists of B 2 R signaling pathway may decrease the harmful consequences of BK activity [6].…”
mentioning
confidence: 99%